Productivity and Profitability Estimates for Sonali Chicken Farms in Rajshahi, Bangladesh - Islam, M. S.; Hossen, M. F.; Rahman, M. M. (Journal of Scientific Research, 2021)
Season- and farm-wise productivity and mortality of Sonali chickens in 53 selected poultry farms from nine Upozillas of Rajshahi District during December 2018 and November 2019 were assessed. Results revealed that, on average, small farms produced 775, medium farms 1828 and large farms 3442 marketable live birds. Mortality was recorded in the following order: small farms > medium farms > large farms. Highest number of birds was produced in spring followed by winter, summer and rainy season, whereas the highest mortality was recorded in winter followed by rainy, summer and spring. Birds reared in smaller farms consumed greater amount of feed compared to those reared in larger farms. Consequently, the live weights, edible weights and edible ratios of the chickens differed significantly due to the farm size. Season-wise variations were significant for day-old chick price, gross return per bird and benefit-cost ratio. Farm-wise variations in the profitability components demonstrated that all the components of the large farms were significantly higher than those of the medium and small farms. With regard to the commercial poultry enterprise of the country, therefore, the present findings on Sonali chicken farming in Rajshahi District are quite encouraging from productivity, profitability and sustainability points of views.